Convergence of cultural traits with time-varying self-confidence in the Panebianco (2014) model: A corrigendum - Fabrizio Panebianco; Anja Prummer; Jan-Peter Siedlarek (Queen Mary University of London, School of Economics and Finance, 2017)
We highlight that convergence in repeated averaging models commonly used to study cultural traits or opinion dynamics is not equivalent to convergence in Markov chain settings if transition matrices are time-varying. We then establish a new proof for the convergence of cultural traits in the model of Panebianco (2014) correcting the existing proof. The new proof provides novel insights on the long-run outcomes for inessential individuals. We close with a discussion of conditions for convergence in repeated averaging models with time-varying transition matrices.
Keywords: D83; D85; Z13; 330; Cultural transmission; Continuous cultural traits; Social networks; Opinion dynamics